Antibiotics combined with vaginal probiotics in the embryo transfer cycle of infertile patients with chronic endometritis - Hu, Ping; Chen, Mengyue; Zhu, Lu; Song, Bing; Wang, Chao; He, Xiaojin; Li, Guanjian; Cao, Yunxia (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionChronic endometritis (CE) is a prolonged, mild inflammation of the endometrial lining. This study investigated the impact of the impact of antibiotic treatment combined with vaginal Lactobacillus on pregnancy outcomes in infertile patients with CE during frozen embryo transfer (FET) cycles.MethodsA retrospective analysis was performed on the clinical data of 7,385 patients who underwent FET. After applying the inclusion and exclusion criteria, 254 patients diagnosed with CE were eligible for inclusion. Of these, 119 patients received antibiotics alone, whereas 135 were treated with a combination of doxycycline and vaginal Lactobacillus. All patients underwent embryo transfer within 6 months following treatment. The general characteristics and pregnancy outcomes of the first FET cycle post-treatment were compared between the two groups.ResultsThere were no statistically significant differences between the two groups in terms of general characteristics, clinical pregnancy rate, early miscarriage rate, and ectopic pregnancy rate. Patients who received a combination of doxycycline and Lactobacillus showed a higher biochemical pregnancy rate compared to those who received doxycycline alone, though this difference was not statistically significant (70.37% vs. 64.71%, P=0.313). Furthermore, the incidence rate of premature rupture of membranes was lower in the doxycycline-Lactobacillus group than in the doxycycline group (50.00% vs 33.33%, P=0.037).ConclusionsAlthough this study observed the potential benefits of the antibiotic and vaginal probiotic treatment regimen in increasing the biochemical pregnancy rate and reducing the incidence of premature rupture of membranes, the current findings are insufficient to recommend the combined use of antibiotics and vaginal Lactobacillus as an intervention to improve reproductive outcomes in infertile patients with CE.